2014
DOI: 10.1021/bm401906p
|View full text |Cite
|
Sign up to set email alerts
|

RVG-Peptide-Linked Trimethylated Chitosan for Delivery of siRNA to the Brain

Abstract: In this work, a peptide derived from the rabies virus glycoprotein (RVG) was linked to siRNA/trimethylated chitosan (TMC) complexes through bifunctional PEG for efficient brain-targeted delivery of siRNA. The physiochemical properties of the complexes, such as siRNA complexing ability, size and ζ potential, morphology, serum stability, and cytotoxicity, were investigated prior to studying the cellular uptake, in vitro gene silencing efficiency, and in vivo biodistribution. The RVG-peptide-linked siRNA/TMC-PEG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 24 publications
1
74
0
Order By: Relevance
“…30,[33][34][35] In addition, the nanoparticles used here are formed by self-assembly, whereas others use conjugation of the peptide by covalent bonds on the surface of the delivery vectors. 36,37 However, this does not imply that our RVG …”
Section: Ex Vivo and In Vivo Administration Of Rvg-containing Nanocommentioning
confidence: 86%
See 1 more Smart Citation
“…30,[33][34][35] In addition, the nanoparticles used here are formed by self-assembly, whereas others use conjugation of the peptide by covalent bonds on the surface of the delivery vectors. 36,37 However, this does not imply that our RVG …”
Section: Ex Vivo and In Vivo Administration Of Rvg-containing Nanocommentioning
confidence: 86%
“…No silencing of mouse BACE1 was detected following intravenous injections ( Figure 5D), unlike other reports that showed silencing even when the RVG/siRNA were delivered by intravenous injections. 30,[33][34][35] Other recent research showed nanoparticle deposition in the brain, but it did not examine the silencing effects there, 36 or it assessed increased enzymatic activity following β-galactosidase administration. 37 The lack of silencing following the intravenous administration of RVG-containing nanoparticles could be due to differences in both the amount of dose and the number of doses delivered, as we used a single 16 μg or 50 μg dose, whereas others use 50-150 μg for up to four doses.…”
Section: Ex Vivo and In Vivo Administration Of Rvg-containing Nanocommentioning
confidence: 99%
“…Hydrogels can be of natural or synthetic origin and include agarose (Balgude et al, 2001; Bellamkonda et al, 1995a, 1995b; Cullen et al, 2007a; Dillon et al, 1998; O'Connor et al, 2001), collagen type I (Coates and Nathan, 1987; Coates et al, 1992; Krewson et al, 1994; O'Connor et al, 2000a; O'Shaughnessy et al, 2003), hyaluronic acid (Brännvall et al, 2007, 2007; Hou et al, 2006; Pedron et al, 2013; Tian et al, 2005), N -(2-hydroxypropyl) methacrylamide (HPMA) (Woerly et al, 1990, 1991), poly(ethylene glycol) (PEG) (Pedron et al, 2013; Wang et al, 2014; Zustiak et al, 2013), chitosan (Gao et al, 2014; Leipzig et al, 2011; McKay et al, 2014), alginate (Frampton et al, 2011; Kuo and Chang, 2013; Matyash et al, 2012; Mosahebi et al, 2003), silk fibroin (Benfenati et al, 2010, 2012; Hopkins et al, 2013; Hu et al, 2013; Kim et al, 2010; Tien et al, 2013; Zhang et al, 2012) and methylcellulose (Stabenfeldt and LaPlaca, 2011; Tate et al, 2001), Table 2 .…”
Section: Designing the Ecmmentioning
confidence: 99%
“…Upon systemic intravenous administration, these complexes were able to transvascularly deliver siRNA to the brain through clathrin- and caveolae-mediated endocytosis by endothelial cells, which lead to extended lives of encephalitic mice. The RVG peptide can also modulate the accumulation of larger vehicles and has delivered macro-structures such as PAMAM dendrimers (Liu et al, 2009), liposomes (Pulford et al, 2010), chitosan nanoparticles (Gao et al, 2014), poly(mannitol- co -PEI) complexes (Park et al, 2015) and exosomes (Alvarez-Erviti et al, 2011) across the BBB and into the brain parenchyma. Other targeting agents have included: angiopep, a peptide that binds to low-density lipoprotein receptor-related protein-1 (Ke et al, 2009); lactoferrin, an iron-binding protein of the transferrin family (Huang et al, 2008, 2010); leptin, a peptide that binds to leptin receptor in different parts of the brain (Liu et al, 2010); chlorotoxin, a scorpion-derived venom that is a specific marker for gliomas (Costa et al, 2013); TGN peptide, a BBB targeting peptide isolated by phage display (Qian et al, 2013); and LIMK2 NoLs peptide, a nucleolar translocation signal sequence derived from the LIM Kinase 2 protein (Yao et al, 2015).…”
Section: Systemic Deliverymentioning
confidence: 99%